Relative effects of climate and litter traits on decomposition change with time, climate and trait variability. (6th November 2020) - Canessa, Rafaella; van den Brink, Liesbeth; Saldaña, Alfredo; Rios, Rodrigo S.; Hättenschwiler, Stephan; Mueller, Carsten W.; Prater, Isabel; Tielbörger, Katja; Bader, Maaike Y.
Abstract: Climate and litter quality drive litter decomposition, but there is currently little consensus on their relative importance, likely because studies differ in the duration, the climatic gradients and variability in litter‐trait values. Understanding these drivers is important because they determine the direct and indirect (via vegetation composition) effects of climate change on decomposition and thereby on carbon and nutrient cycling. We studied how microclimate (soil moisture and temperature) and litter traits interactively affect litter mass loss, by using a reciprocal litter translocation experiment along a large climatic gradient in Chile. We followed decomposition for 2 years and used 30 plant species with a wide spectrum of functional‐trait values. Litter traits had a strong impact on litter decomposition across the gradient, while an increase in decomposition with soil moisture was observed only in the wettest climates. Overall, soil moisture increased considerably in importance, relative to trait effects, at later decomposition stages, from c . 15% of the importance of traits after 3 and 6 months to c . 110% after 24 months. Moreover, analysing subsets of the 30 species showed that trait effects on litter decomposition gained in importance when including a greater variation in trait values. Synthesis . The relative effects of litter traits and climate on decomposition depend on the ranges in climate and litter traits considered and change with time. Our study emphasizes the critical role of representative ranges in climate and functional trait values for understanding the drivers of litter decomposition and for improving predictions of climate‐change effects on this important ecosystem process. Abstract : The relative effects of litter traits and climate on decomposition depend on the ranges in climate and litter traits considered and change with time. Our study emphasizes the critical role of representative ranges in climate and functional trait values for understanding the drivers of litter decomposition and for improving predictions of climate‐change effects on this important ecosystem process. Resumen: El clima y la calidad de la hojarasca promueven la descomposición de ésta, sin embargo, actualmente existe poco consenso respecto a la importancia relativa de estos factores, probablemente debido a que los diversos estudios difieren en su duración, los gradientes climáticos y la variabilidad de rasgos de la hojarasca considerados. Entender estos factores reguladores es importante, pues determinan los efectos directos e indirectos (a través de la composición de la vegetación) del cambio climático sobre la descomposición y, por ende, sobre el ciclaje de carbono y nutrientes. Estudiamos cómo el microclima (humedad y temperatura del suelo) y los rasgos funcionales de la hojarasca afectan la pérdida de biomasa de ésta, utilizando un experimento con translocación recíproca de hojarasca a lo largo de un gradiente climático en Chile. Estudiamos la descomposición por dos años, usando 30 especies de plantas que presentan un amplio espectro de rasgos funcionales. Los rasgos funcionales de la hojarasca tuvieron un fuerte efecto sobre la descomposición a lo largo de todo el gradiente, mientras que la humedad del suelo sólo incrementó la descomposición en los climas más húmedos. En general, la importancia de la humedad del suelo en la descomposición incrementó en relación al efecto de los rasgos, en etapas tardías del proceso de descomposición, representando aprox. un 15% de la importancia de los rasgos luego de 3 y 6 meses, y un 110% luego de 24 meses. Además, al analizar subconjuntos de las 30 especies se demostró que el efecto de los rasgos sobre la descomposición de la hojarasca gana importancia cuando se incluye una mayor variación en los valores de estos rasgos. Síntesis . Los efectos relativos de los rasgos funcionales de la hojarasca y del clima sobre la descomposición dependen del rango de climas y de rasgos considerados, y cambian a lo largo del tiempo. Nuestro estudio enfatiza el rol crítico que juega una amplitud representativa, tanto de climas como de rasgos funcionales, para comprender los factores determinantes de la descomposición de la hojarasca y mejorar así las predicciones de los efectos del cambio climático sobre este importante proceso ecosistémico.